(untitled) (MAUSAM, 1977)
A mathematical model is proposed for the planning of cooling ponds used for dissipation of waste heat from heated discharge water of Power Generating Stations. This dissipation of waste heat is found to be mainly dependent on wind speed and water temperature, negligibly influenced by air temperature and humidity and is independent of solar radiation. The model’s special application is where the water resources are limited and need for recycling of water used for cooling the condenser waters of the power station is necessary. The models show that the acreage requirements of the cooling ponds of such types of the order of 1.0 to 2.5 acres/Mw (e) during the hotter months at Bombay. Data was also collected at Tarapur Atomic Power Station’s discharge channel and the model calculations compared well with the actual temperature fall in the channel observed during low tide.